ANALISIS KOMPETENSI KEPRIBADIAN GURU TK SE KECAMATAN TALAMAU KABUPATEN PASAMAN BARAT - Tris Madona; Daviq Chairilsyah; Wusono Indarto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This descriptive study aims to reveal the personality of the teacher competency kindergarten Talamau at Subdistrict of West Pasaman. The sample in this study is a kindergarten teacher Talamau at Subdistrict of West Pasaman many as 49 teachers. The data collection technique using a questionnaire containing statements about the competence of the teacher's personality Early Childhood Education. Analysis data technique using large-scale testing and analysis of statistical methods with SPSS for Windows Ver. 20. Based on the results of this study concluded that personal competence kindergarten teachers throughout the at Subdistrict Talamau West Pasaman as many as 49 teachers earn a percentage 85.22%, in the category